Analysis of rotational stiffness of steel-concrete composite beams for lateral-torsional buckling. (1st November 2019) - Dietrich, Mateus Zimmer; Calenzani, Adenilcia Fernanda Grobério; Fakury, Ricardo Hallal
Highlights: Continuous (and semi) composite beams may suffer lateral-torsional buckling (LTB). The rotational stiffness of the beams is an important property for design against LTB. A FE model for determine the rotational stiffness of composite beams is presented. An adjustment is proposed in Eurocode procedure to obtain the slab stiffness. The rotational stiffness can be obtained in function only of the web stiffness. Abstract: In hogging bending moment regions of continuous and semi-continuous steel-concrete composite beams, the bottom flange of the steel profile is compressed, and if the web is not rigid enough to avoid lateral bending, it will undergo distortion, causing a lateral displacement and a rotation of the compressed flange. These displacements characterize the mode of instability called lateral-torsional buckling (LTB). European Standard EN 1994-1-1:2004 presents a procedure to verify the ultimate limit state of LTB based on the elastic critical moment that depends on the rotational stiffness of the composite beam. In this paper, numerical models, simulating the inverted U-frame model for inner and edge composite beams, were developed with the support of the software ANSYS to evaluate the procedure presented by EN 1994-1-1:2004 to calculate the rotational stiffness of steel-concrete composite beams. The numerical results agreed reasonably well with the predictions of EN 1994-1-1:2004, however, the accuracy of the analytical procedure can be improved by a small adjustment in the slab rotational stiffness equation. It was also observed that, in certain situations, the rotational stiffness of composite beams can be determined in a simplified manner only as function of the value of the rotational stiffness of the web of the steel profile, without loss of precision.